Modelos auto-similares para rádio fontes extragalácticas - Araújo, Fábio César de (2008)
This work is a detailed study of self-similar models for the expansion of extragalactic radio sources. A review is made of the deﬁnitions of AGN, the uniﬁed model is discussed and the main characteristics of double radio sources are examined. Three classiﬁcation schemes are outlined and the self-similar models found in the literature are studied in detail. A self-similar model is proposed that represents a generalization of the models found in the literature. In this model, the area of the head of the jet varies with the size of the jet with a power law with an exponent γ. The atmosphere has a variable density that may or may not be spherically symmetric and it is taken into account the time variation of the cinematic luminosity of the jet according to a power law with an exponent h. It is possible to show that models Type I, II and III are particular cases of the general model and one also discusses the evolution of the sources radio luminosity. One compares the evolutionary curves of the general model with the particular cases and with the observational data in a P-D diagram. The results show that the model allows a better agreement with the observations depending on the appropriate choice of the model parameters.